2015
DOI: 10.1016/j.febslet.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The steroid receptor RNA activator protein (SRAP) controls cancer cell migration/motility

Abstract: a b s t r a c tThe steroid receptor RNA activator gene (SRA1) produces both a functional RNA (SRA) and a protein (SRAP), whose exact physiological roles remain unknown. To identify cellular processes regulated by SRAP we compared the transcriptome of Hela and MDA-MB-231 cancer cells upon depletion of the SRA/SRAP transcripts or overexpression of the SRAP protein. RNA-seq and Ontology analyses pinpointed cellular movement as potentially regulated by SRAP.Using live cell imaging, we found that SRA/SRAP depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Deep-sequencing experiments revealed many examples of genes producing both protein-coding and noncoding transcripts by alternative splicing. However, so far, only very few reports demonstrate a functional role for both the noncoding RNA(s) and the protein(s) encoded by transcripts derived from the same gene [ 15 , 16 ]. It is tempting to speculate that such dual usage of transcripts is more frequent than anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Deep-sequencing experiments revealed many examples of genes producing both protein-coding and noncoding transcripts by alternative splicing. However, so far, only very few reports demonstrate a functional role for both the noncoding RNA(s) and the protein(s) encoded by transcripts derived from the same gene [ 15 , 16 ]. It is tempting to speculate that such dual usage of transcripts is more frequent than anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…As it was mentioned, SRA1 is a nuclear receptor that encodes both non-coding (lncRNA SRA1) and coding (SRAP) products result from alternative splicing 7,8,10. It is believed that both transcripts are functional and regulate several molecular pathways especially through ERs 7,9,11.…”
Section: Discussionmentioning
confidence: 99%
“…Each PCR reaction comprised of 10 µl 2X RealQ-PCR Master Mix ® (Ampliqon, Odense, Denmark), 1 µl cDNA (≥10 ng), 0.5 µl of each primer (5 pmol) and 7 µl of nuclease-free water in a total volume of 20 µl reaction mixture. Primers for amplification of SRA1 lncRNA were obtained from a previous study 8…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, SRAP levels were significantly higher in ERα-positive and PR-positive breast cancer biopsies, identifying SRAP as a potential new prognostic marker for breast cancer patients ( 84 ). A recent study further indicated that overexpressing SRAP increases breast cancer cell motility ( 85 ).…”
Section: Sra and Human Diseasementioning
confidence: 99%